THE CLINICAL COURSE OF UREMIA IN PATIENTS WITH RHEUMATOID ARTHRITIS AND ITS IMPACT ON COMORBID PATHOLOGIES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This analysis explores the clinical features, underlying mechanisms, and treatment considerations of uremia in rheumatoid arthritis patients, focusing on its effects on cardiovascular, musculoskeletal, and hematologic comorbidities. Evidence shows that these patients are at higher risk for chronic kidney disease and uremic complications due to systemic inflammation, drug-related nephrotoxicity, and accelerated atherosclerosis. A comprehensive understanding of these factors is vital for effective management and improved patient outcomes.